PEMERTAHANAN BAHASA SUNDA DI KECAMATAN BINONG KABUPATEN SUBANG: SUATU KAJIAN SOSIOLINGUISTIK (THE MAINTENANCE OF SUNDANESE LANGUAGE IN BINONG DISTRICT, SUBANG REGENCY: A SOCIOLINGUISTIC STUDY) - Nunung Yuliantini; Cece Sobarna; Wahya Wahya (Metalingua: Jurnal Penelitian Bahasa, 2021)
This research examines about matters and language choice, the preservation pattern and strategy of Sundanese language, and the determinants that influence of Sundanese language preservation. in Binong District, Subang Regency. This research was conducted by considering two approaches, those were theoretical approach and methodological approach. Theoretically, the approach used in this research is a sociolinguistic approach. Methodologically, this research used a combination of quantitative and qualitative methods. The data sources extracted in this study consisted of main data in the form of respondents’ answers to the questionnaire, respondents’ answer during the interview, and notes during observation; as well as additional or secondary data sources, in the form of supporting documents such as the informant’s age, educational background, and environment. Data were obtained from respondents with certain age criteria (children, adolescence, adults, and the elderly) according to a questionnaire designed to support the study towards the identified problems. The data used in this study comes from the use of Sundanese in the communities of Nangerang Village, Cicadas, Karangsari, and Binong Village. A total of 160 respondents spread across four villages (Nangerang Village, Cicadas, Karangsari, and Binong Village) were used as research samples.The results showed that: (1) The attitudes and language choices of the Nangerang Village, Cicadas, Karangsari, and Binong Village people were based on four age groups, those are: children 6-12 years, adolescence 13-21, adults 22-35, and the elderly 36-70 years, in general, from all respondents, most of them still use Sundanese as their main language in communication; (2) the pattern and strategy of the Sundanese language preservation on the eight domains of use, Sundanese is still consistently used by Sundanese speakers in Binong sub-district, at various age levels, starting from the age of children, adolescents, adults, and the elderly, in the eight domains of use, namely the family domain. neighborliness and friendship, transactions, traditions/culture, education, government, religion, and topics of discussion; and (3) Internal factors extremely influence the preservation of Sundanese language, especially depending on the positive attitude of Sundanese language in personal, family environment, and close relatives who make Sundanese language accustomed to the life of the people. External factors have made the use of Sundanese language marginalized and replaced by Indonesian and local Javanese.